Leadership, Compensation, and Employee Performance: Evidence from Leasing Companies - Habibie, Haq Muhammad Hamka; Rusli, Moch. (Jurnal Ragam Pengabdian, 2024)
Human resources are a critical organizational asset in supporting sustainable company performance, particularly in service-oriented industries such as leasing. Effective leadership and appropriate compensation are two important managerial factors that can shape employee attitudes, satisfaction, and performance. This study examines the influence of leadership and compensation on employee performance, with job satisfaction considered as a mediating variable, in the context of PT Mitsui Leasing Capital Indonesia. A quantitative research design was employed using primary data collected through questionnaires distributed to 193 employees. Secondary data from relevant journals and articles were also used to strengthen the theoretical foundation of the study. The findings indicate that leadership and compensation have a positive relationship with employee performance and employee satisfaction. In addition, job satisfaction has a positive effect on employee performance. The results further suggest that job satisfaction plays an indirect mediating role in the relationship between leadership, compensation, and employee performance. These findings highlight the importance of strengthening leadership practices and designing fair compensation systems to enhance employee satisfaction and improve organizational performance. This study contributes to human resource management literature by providing empirical evidence from the leasing industry and offers practical implications for companies seeking to improve employee productivity through managerial and compensation strategies.